A randomized trial of a wearable UV dosimeter for skin cancer prevention - Dumont, Emmanuel L. P.; Kaplan, Peter D.; Do, Catherine; Banerjee, Shayak; Barrer, Melissa; Ezzedine, Khaled; Zippin, Jonathan H.; Varghese, George I. (Frontiers in Medicine, 2024)
Non-melanoma skin cancer (NMSC) is the most prevalent cancer in the United States. Despite guidelines on ultraviolet (UV) avoidance, it remains difficult for people to assess their exposure, as UV is invisible and the onset of UV-induced symptoms is delayed.In a prospective randomized trial, 97 elderly patients with a history of actinic keratoses (AK) were followed over six months. Fifty patients received UV counseling from a dermatologist and a wearable UV dosimeter that provided real-time and cumulative UV exposure. Forty-seven patients received only UV counseling from a dermatologist.Over 75% of participants recorded UV exposure at least once a week during the summer. After 6 months of intervention, when comparing the device group to the control group, we observed a nonsignificant 20% lower ratio of incidence rates of AKs (95% CI = [-41%, 55%], p-value = 0.44) and a significant 95% lower ratio of incidence rates of NMSCs (95% CI = [33%, 99.6%], p-value = 0.024). Surveys demonstrated that the control group's score in self-perceived ability to participate in social activities significantly increased by 1.2 (p-value = 0.04), while in the device group, this score non-significantly decreased by 0.9 (p-value = 0.1). We did not observe changes, or between-group differences, in anxiety and depression surveys.This pilot clinical trial has a short duration and a small sample size. However, device adherence and quality of life questionnaires suggest a smartphone-connected wearable UV dosimeter is well accepted by an elderly population. This trial also indicates that a wearable UV dosimeter may be an effective behavioral change tool to reduce NMSC incidence in an elderly population with a prior history of AKs.The trial was registered on clinicaltrials.gov under the identification NCT03315286 on October 20, 2017.